Numerical Analysis of the Steady-state Isothermal Elastohydrodynamic Lubrication of Gear Rack Transmission - Xu Caihong; Wang Youqiang; Fan Xiaomeng; Wang Tao; Wang Jian (Jixie chuandong)
The Gear rack is widely used in modern machinery,but it is easy to produce noise,wear and tooth surface scoring etc during the transmission process. Through research of the theory of mechanism lubrication to reduce the probability of tooth wear and tooth scoring during the transmission process. On the basis of the existing EHL theory,the EHL numerical solution of gear rack is obtained by utilizing the multi- grid method and the distribution of dimensionless pressure and film thickness under the effect of different mesh point,different modification coefficient,different ratio of line to angel and different modulus of the gear rack transmission mechanism are discussed. The results show that the position of mesh point,modification coefficient,ratio of line to angle and modulus are all have impacts on the oil pressure and film thickness. Eventually come to the conclusion that the meshing point is the dangerous point during the transmission process,the positive shift makes the oil film thicker while the negative shift makes the oil film thinner,the more ratio of line to angle and modulus,the smaller pressure and the thicker the film thickness.